Persepsi Generasi Milenial Terhadap Gerakan 30 September 1965 - Samson Ganda J. Silitonga (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The 30 September 1965 Movement was a momentum for political change in Indonesia after Independence on 17 August 1945. Six generals, plus a first officer, were killed in that incident. One of them was the KSAD, Lieutenant General Ahmad Yani, five deputies from the KSAD, as well as a bodyguard for the Minister of Defense/Chief of Staff of the Armed Forces (KSAB). The killer of the victim who was called the 'Hero of the Revolution' was a troop from the Tjakrabirawa/ Presidential Guard Regiment led by Lieutenant Colonel Untung. Almost 60 years have passed, what is the perception of the millennial generation towards this event and its impact on the current Indonesian political atmosphere? As a teacher of Indonesian Ideology and Politics, I have an interest in detecting that perception in order to build an up-to-date analysis, using the most theoretical approach possible, and to build new conclusions that are relevant even if tentative. One theory that is maintained and updated is Social Change from Thomas S. Kuhn. So far, Kuhn's Theory of Social Change emphasizes that every society must always experience Social Change, which is covered in various factors and Normal Science. Several factors were mentioned, such as Economy, Politics, Culture and Technology. At least the four factors are quite dominant, although in the Indonesian context the military and religious factors are also very prominent. It should also be mentioned that according to Sigmund Freud (1856-1939) society determines the individual more than the other way around. If so, Social Change is also caused by the behavior and dynamics of society when individuals are no longer influential and decisive. On the other hand, society is also dealing with a state that is not single. Thus the question arises, how can all these elements become objective conditions that can be explained thoroughly? Based on these two approaches, I try to look at the problem further, accompanied by a method that seems appropriate and scientifically justifiable.